Analysis of Lactobacillus Products for Phages and Bacteriocins That Inhibit Vaginal Lactobacilli - Tao, Lin (Hindawi Publishing Corporation, 1997)
Objective: Bacterial vaginosis is associated with an unexplained loss of vaginal lactobacilli. Previously, we have identified certain vaginal lactobacilli-released phages that can inhibit in vitro other vaginal lactobacilli. However, there is no apparent route for phages to be transmitted among women. The purpose of this study was to identify whether certain Lactobacillus products commonly used by women release phages or bacteriocins that can inhibit vaginal lactobacilli. Methods: From 26 Lactobacillus products (2 acidophilus milks, 20 yogurts, 3 Lactobacillus pills, and 1 vaginal douche mix), lactobacilli were isolated with Rogosa SL agar (Difco, Detroit, MI). From these lactobacilli, phages and bacteriocins were induced with mitomycin C and tested against a collection of vaginal Lactobacillus strains. Results: From the 26 products, 43 Lactobacillus strains were isolated. Strains from 11 yogurts released phages, among which 7 inhibited vaginal lactobacilli. Eleven strains released bacteriocins that inhibited vaginal lactobacilli. While about one-half of the vaginal strains were lysed by bacteriocins, less than 20% were lysed by phages. Conclusions: Some vaginal lactobacilli were inhibited in vitro by phages or bacteriocins released from Lactobacillus products used by women, implying that vaginal lactobacilli may be reduced naturally due to phages or bacteriocins from the environment.